Предмет: Математика,
автор: 0Знающий0
1) (√27-2)(2-3√3)
2) (5√3+√27)÷√3
3)(√5-1)²-(2√5+1)²
Ответы
Автор ответа:
0
1) (√27-2)(2-3√3)= 2√27-3√81-4+6√3=6√3-27-4+6√3=12√3-31
2) (5√3+√27)÷√3=(5√3+3√3)÷√3= 8√3÷√3=8
3) (√5-1)²-(2√5+1)=(√5-1+2√5+1)×(√5-1-2√5-1)=-15-6√5
2) (5√3+√27)÷√3=(5√3+3√3)÷√3= 8√3÷√3=8
3) (√5-1)²-(2√5+1)=(√5-1+2√5+1)×(√5-1-2√5-1)=-15-6√5
Похожие вопросы
Предмет: Английский язык,
автор: MazhorOmega
Предмет: Английский язык,
автор: Аноним
Предмет: Русский язык,
автор: bfbbgchg
Предмет: Физика,
автор: zxxzccx